Новый вид мух-пестрокрылок рода Rhagoletis Loew (Diptera, Tephritidae) из Таджикистана - Рихтер, В.А. (Вестник зоологии, 1974)
The description of the new species of the genus Rhagoletis Loew-Rh. emiliae sp. n. is given. The new species differs from all known European and Asiatic species in yellow thorax and abdomen, absence of the short band beginning on costa between basal and subapical bands and other features of the wing pattern.